Study of albumin and anti-snap25 mixtures on lipid monolayers using the langmuir-blodgett technique / Gew Lai Ti - Gew , Lai Ti (2017)
Lipid-protein interactions are essential for biological membrane functions. Lipid composition and its molecular packing are the key determinants for distinct functions of the biological membrane. A better knowledge of lipid-protein interactions may be useful for preparing mixed lipid systems, for example, targeted drug-delivery systems. To elucidate the interactions between proteins and the surrounding lipids, C18 fatty acids with different degrees of saturation in their hydrocarbon chain, namely stearic acid (SA), oleic acid (L1), linoleic acid (L2), and linolenic acid (L3), and phospholipids with saturated hydrocarbon chain but different headgroup, such as sucrose stearate (SS), 1,2-distearoyl-sn-glycero-3-phosphoglycerol (DSPG), 1,2-distearoyl-sn-gylcero-3-phosphocholine (DSPC), and dipalmitoylphosphatidylcholine (DPPC) were used to create a monolayer mimicking a half bilayer membrane to be incorporated with various concentrations of an integral protein, bovine serum albumin (BSA) and a polyclonal antibody, Anti-SNAP25 (AS25) onto the respective monolayer using the Langmuir-Blodgett technique accompanied by atomic force microscopy (AFM) imaging. Lipid-protein interactions that occur in the mixed system can be studied from data on miscibility, compressibility and thermodynamic stability from the isotherms obtained. The analyzed data would give an insight into intermolecular interactions between the lipid and protein, thereby providing useful information on the different ways proteins associate with lipid membranes. The cis-double bonds in unsaturated lipids (L1, L2 and L3) have kinks in their molecular conformation and thus could not pack as tightly and uniformly as SA. The bends and kinks in the molecular structure may interfere with the packing of the lipid monolayer which will promote fluidity as shown in the analyzed compressibility modulus (Cs-1) data. The headgroup of phospholipids with different functional groups has distinctive intermolecular interaction with both proteins. Gibbs free energy of mixing ( ) values of lipids/BSA were found to be more negative than lipids/AS25 that explained how the integral and membrane-bound protein are embedded in membranes. The amount of protein incorporated into the monolayer strongly affected the thermodynamic properties of the membrane. AFM surface roughness analyses also indicated that BSA homogenously penetrated in between the lipid membrane and AS25 molecules are strongly bounded on the surface membrane as predicted by the energetic data. Subsequently, Langmuir energetic findings were compared to fatty acid DPPC liposomes preparation. The stability of liposomes was characterized by their mean particle size and zeta potential for 28 days. The formation of liposomes was confirmed by transmission electron microcopy (TEM) images. DPPC/DP/AS25 liposome system was found more stable than L1/DP/AS25. The particle size and zeta potential measurements of DPPC/DP/AS25 liposomes remained nearly constant for 28 days and 14 days respectively. This stability showed agreement with the LB findings as large negative values of were obtained for DPPC/DP/AS25 mixed monolayer.